Evaluasi Materi Ajar Bahasa Inggris Cambridge IGCSE dan A/AS Level Sebagai Materi Acuan Program SBI tingkat SMA di Indonesia, Studi Kasus SMAN 70 Jakarta - Ria Herwandar (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2011)
A law no 20/2000 paragraph 50, article 3 has been enacted by the Ministry of education concerning the implementation of International class in high Schools throughout Indonesia. The purpose of this regulation is to standardize the quality of the Indonesian students educational qualification to those of students abroad. As a result, Cambridge International Examinations IGCSE, A/AS Level have become popular to the majority of Indonesian High Schools, especially  for subjects such as Mathematics, English, Physics, Biology and Chemistry. This research will look upon the develompment of school implementation of IGCSE, A/AS Level of English Language in SMA N 70 jakarta as a case study. Through several assessments of students IGCSE, A/AS Level tests, interviews, questionners and material evaluation, a reliable findings will be identified. At the end, ways of effective learning and teaching of IGCSE, A/AS Level  for Indonesian High Schools will be suggested.